美法仑联合大剂量地塞米松一线治疗原发性轻链型淀粉样变的疗效分析 (Zhonghua Xue Ye Xue Za Zhi, 2018)
OBJECTIVE: To evaluate the response of oral melphalan plus high-dose dexamethasone (MDex) for patients with primary light chain amyloidosis (pAL). METHODS: Clinical data, hematological and organ responses, and survival of 76 patients with pAL who had received MDex from January 2009 to July 2017 were retrospectively analyzed. RESULTS: Of 76 patients (47 males and 29 females with the median age of 56 [range, 20–74] years old), 19.70% patients were defined as Mayo 2004 stage 3, involvement of more than or two organs was presented in 65 (85.53%) patients. Among 60 response evaluable patients, overall hematological response was 48.33% with complete response of 20.00% and very good partial response of 20.00%, respectively. The median time to the hematological response was 5 (range, 1–15) months. 36.67% patients achieved organ response. After the median follow up of 23(range, 1–113) months for surviving patients, median progression-free survival (PFS) and overall survival (OS) were 34 and 43 months, respectively. In a three months landmark analysis, the median rates of PFS and OS were 46 and 65 months, respectively. The median OS rates of patients with Mayo 2004 stage 3 and non Mayo 2004 stage 3 were 5 and 65 months (P=0.001), respectively. CONCLUSION: MDex was an effective treatment for patients with early stage pAL, but was not suitable for those with severe cardiac involvement.